Investigating the effect of self-trapped holes in the current gain mechanism of β-Ga2O3 Schottky diode photodetectors - Akyol, Fatih (Tubitak Scientific & Technological Research Council Turkey, 2021)
Monoclinic gallium oxide (beta-Ga2O3) has found great research interest in solar blind photodetector (SBP) applications due to its' bandgap similar to 4.85 eV and availability of high quality native crystal growth. Applications including missile guidance, flame detection, underwater/intersatellite communication and water purification systems require SBPs. beta-Ga2O3 SBPs with high responsivity values have been published indicating internal gain in these devices. The gain has been attributed to accumulation of self-trapped hole (STH) below Schottky metal which the lowers Schottky barrier in these devices based on some approximations rather than a proper device simulation. In this paper, technology computer-aided design (TCAD) simulation of beta-Ga2O3 SBPs are performed to numerically investigate the effect of low hole mobility STHs on Schottky barrier lowering (SBL). The simulations revealed that based on the theoretical hole mobility of 1 x 10(-6) cm(2) V-1 s(-1), photoconductive gain in beta-Ga2O3 based photodetectors cannot be attributed to STH related hole accumulation near Schottky contact. It is found that hole mobility in the range of 1 x 10(-10) cm(2) V-1 s(-1) -1 x 10(-12) cm(2) V-1 s(-1) is required to induce similar to 0.3 eV of SBL potential. Unless such low hole mobility is reported either experimentally or theoretically, it is not reasonable to attribute gain to STH formation in these devices.
Keywords: Gallium oxide; beta-Ga2O3 self-trapped holes; photodetector; Schottky barrier lowering; photoconductive gain; simulation; HIGH RESPONSIVITY; SINGLE-CRYSTALS; SEMICONDUCTOR; FILMS; GAN; Physics